Implementasi Metode Inquiri Dalam Pembelajaran Ipa - Zain, Ahmad Arifin (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
Inquiry method which is done by the teacher is including several steps: [1] orientation, theteacher gives apperception, motivation, and explain the learning goal; [2] formulating theproblem, the teacher gives some questions to the students; [3] formulating the hypothesis,from the question will give hypothesis or temporary answer; [4] collecting data, explain thelearning goal which will be learned later, then share the student’s work sheet to eachgroups and read the working steps which will be done for hypothesis test; [5] testing thehypothesis, guiding, monitoring the students, directing the student to write theexperiment result; and [6] formulating the conclusion, student are reading their discussionresult and the teacher give enforcement